2015
DOI: 10.5603/piap.2015.0047
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution and Asthma in Children at Delhi, India

Abstract: Introduction: Several studies in developed countries have shown association between indoor air pollution and asthma in children. The present research was undertaken to study this association at Delhi, India. Material and methods: This study took place at Delhi, capital of India. Eight locations based on the source of pollution such as industrial, residential and villages were included. Recording of the demographic profile and clinical examination of each child was conducted at their residence. Indoor SO 2 , NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
1
19
0
2
Order By: Relevance
“…Para a cultura de Belém isso representa extrema pobreza, demonstrando a vulnerabilidade econômico-social destas famílias, cujos filhos apresentam maior risco de sibilância. Esses dados estão de acordo com pesquisa realizada em país de baixa renda onde se relacionou pobreza com sibilância 16,17 e podem estar relacionados com poluição ambiental intradomiciliar, onde famílias pobres cozinham no mesmo espaço onde vivem e dormem.…”
Section: /9unclassified
“…Para a cultura de Belém isso representa extrema pobreza, demonstrando a vulnerabilidade econômico-social destas famílias, cujos filhos apresentam maior risco de sibilância. Esses dados estão de acordo com pesquisa realizada em país de baixa renda onde se relacionou pobreza com sibilância 16,17 e podem estar relacionados com poluição ambiental intradomiciliar, onde famílias pobres cozinham no mesmo espaço onde vivem e dormem.…”
Section: /9unclassified
“…Another study in industrial area of Delhi revealed that high concentration level of particulate matter containing quartz, carbonate, mica, and several major and trace elements including Si, Cr, Ni, Pb, Zi and Cu an important factor for causing increased asthma among children [15]. Industries play valuable role for increases the concentration of indoor suspended particulate matter and occurrence of asthma in children in developing countries [16,17]. The high values for mean level of indoor SPM was associated with environmental factors in industrial areas of Delhi.…”
Section: Mineral and Chemical Composition Of Indoor Air Pollution Andmentioning
confidence: 99%
“…Paparan zat polutan yang lama dapat menyebabkan batuk, sakit tenggorokan, bronkitis akut maupun kronik, asma, pneumonia dan yang terparah yaitu kanker paru (Getrudis, 2010). Penelitian yang dilakukan oleh Kumar et al (2015) juga menjelaskan, bahwa konsentrasi partikulat (>10 µm) didalam ruangan berhubungan dengan peningkatan gejala asma dan partikulat yang berukuran lebih kecil (<2,5µm) secara nyata berhubungan dengan peningkatan gangguan pernapasan. Hal tersebut juga berpengaruh terhadap anak-anak penderita asma.…”
Section: Pembahasanunclassified